ANALYSIS OF ENCAPSULATED YEAST IN COMPUTATIONAL FLUID DYNAMICS APPROACH - Riani Ayu Lestari; Rianti Indah Lestari (Universitas Lambung Mangkurat, 2019)
Abstract - Computational fluid dynamics of encapsulated yeast has been developed to determine characterization of encapsulated yeast applied for ethanol production from lignocellulose waste. Encapsulated yeast as biologically activate materials enclosed in a semipermeable membrane to protect cell from inhibitor attack. Encapsulated yeast system relates to mass transfer of substrate (glucose) into capsule and out of capsule and fermentation reaction. Modelling of mass transfer was developed to understand capsule performance consisting of 3 parts, cell aggregate, liquid space and thin membrane. Finite element method has been applied to solve partial differential equation of glucose concentration profile against x, y position and t -time in Comsol multhiphysics 3.5a. Capsule geometry was showed in half part capsule, 2D and axis symmetries. Trend line of glucose distribution was effected by thickness membrane that 0.1 mm controlling in mass transfer and cell aggregate of 50%-v of membrane.Keywords: computational fluid dynamics, encapsulated yeast system, glucose mass transfer